(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the ideas of the Khojagon Tariqah and their spiritual and moral significance in building an enlightened society. The Khojagon Tariqah fosters harmony between a person’s nafs and heart, promotes the cultivation of moral values, and ensures social stability, forming the essential spiritual foundation of an enlightened society.